The Apolipoprotein E ε4 Allele-Dependent Relationship Between Serum Lipid Levels and Cognitive Function: A Population-Based Cross-sectional Study - Wei, Shan; Gao, Ling; Jiang, Yu; Shang, Suhang; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Wang, Jingyi; Qu, Qiumin (Frontiers in Aging Neuroscience, 2020)
Objectives: Till now, the effect of serum lipid levels on cognitive function is still controversial. The apolipoprotein E ε4 allele is the most critical genetic risk factor for Alzheimer’s disease and cognitive impairment. Additionally, apolipoprotein E ε4 allele has a major impact on lipid metabolism. The aim of this study was to investigate the apolipoprotein E genotype-dependent relationship between peripheral serum lipid levels and cognitive impairment. Methods: 1273 subjects aged 40-86 years participated in this cross-sectional study. Serum lipid levels and the apolipoprotein E genotype were detected. Mini-mental state examination was used to diagnose the cognitive impairment or not. Univariate and multivariate analyses were used to analyze the relationships between apolipoprotein E genotype, serum lipid levels and cognition function. Results: After controlling for all possible covariates, a significant interaction between low serum high density lipoprotein and the apolipoprotein E ε4 allele on cognitive impairment (Wald's chi-square=4.269, df=1, OR=20.094, p=0.039) was found in the total participants. In apolipoprotein E ε4 carriers, low serum high density lipoprotein was positively associated with cognitive impairment (Wald's chi-square=8.200, df=1, OR=60.335, p=0.004), and serum high density lipoprotein levels were positively correlated with Mini-mental state examination score (r=0.217, df=176, p=0.004). There was no significant correlation between serum total cholesterol, low-density lipoprotein, triglycerides levels and cognitive impairment in either the total participants or apolipoprotein E ε4 carriers/non-carriers. Conclusions: Apolipoprotein E ε4 carriers, but not non-carriers, with lower serum high-density lipoprotein had a higher prevalence of cognitive impairment and a lower Mini-mental state examination score. These results suggest that the apolipoprotein E ε4 allele may affect the relationship between serum lipid levels and cognitive impairment. However, the specific mechanism needs to be further elucidated.